Enhancing Modbus-Rtu Communications for Smart Metering in Building Energy Management Systems - Urrea-Onate, E; Morales-Diaz, C (Hindawi Limited, 2019)
In this work, a method for detecting and correcting errors in Modbus-RTU communications is designed, implemented, and assessed in a smart metering application. This is a low-cost solution for improving communication quality in conventional Modbus-RTU architectures with copper fieldbus. It consists of introducing error detection and correction devices in the network segments most susceptible to errors caused by electromagnetic interference. Experimental validations were conducted and demonstrated the effectiveness of this method for isolating noisy segments in the communication bus, maintaining full compatibility with commercial devices and improving the performance of the entire network. © 2019 Claudio Urrea and Claudio Morales.